Data sharing: A new editorial initiative of the International Committee of Medical Journal Editors. Implications for the Editors´ Network - Alfonso, Fernando; Adamyan, Karlen; Artigou, Jean-Yves; Aschermann, Michael; Boehm, Michael; Buendia, Alfonso; Chu, Pao-Hsien; Cohen, Ariel; Dei Cas, Livio; Dilic, Mirza; et al. (SA Heart Journal, 2017)
The International Committee of Medical Journal Editors (ICMJE) provides recommendations to improve the editorial standards and scientific quality of biomedical journals. These recommendations range from uniform technical requirements to more complex and elusive editorial issues including ethical aspects of the scientific process. Recently, registration of clinical trials, conflicts of interest disclosure, and new criteria for authorship – emphasising the importance of responsibility and accountability – have been proposed. Last year, a new editorial initiative to foster sharing of clinical trial data was launched. This review discusses this novel initiative with the aim of increasing awareness among readers, investigators, authors and editors belonging to the Editors´ Network of the European Society of Cardiology.